A Small-Scale Solar Organic Rankine Cycle Combined Heat and Power System with Integrated Thermal-Energy Storage - Freeman, James; Guarracino, Ilaria; Kalogirou, Soteris A.; Markides, Christos N. (My University, 2016)
In this paper, we examine integrated thermal energy storage (TES) solutions for a particular domestic-scale solar combined heat and power (S-CHP) system based on an organic Rankine cycle (ORC) engine and low-cost non-concentrated solar-thermal collectors. TES is an essential system component for steady operation in climates with high solar irradiance variability. The operating temperature range of the TES solution must be compatible with the solar collector array and ORC engine in order to maximise the overall efficiency of the system. Various combinations of phase change materials (PCMs) and solar collectors are compared and the S-CHP system’s electrical performance is simulated for selected months in the contrasting climates of Cyprus and the UK. The key performance parameter of the ORC engine (net power output) and the required TES volume are compared and discussed. Through the selection of an appropriate PCM it is found that a higher sustained power output per required storage volume can be achieved compared to water as a sensible heat storage medium. The TES solutions that achieve the best summer performance from the ORC engine result in diurnal volume requirements of 20-90 L in Cyprus and 200-400 L in the UK.
Keywords: Ιntegrated thermal energy storage; Domestic-scale solar; Rankine cycle